Die kirchenslavische Übersetzung der Dioptra des Philippos Monotropos. Bd. 1 Überlieferung. Text der Programmata und des ersten Buches - Miklas, Heinz; Fuchsbauer, Jürgen (Holzhausen, 2013)
This volume is dedicated to the Church Slavonic version of the Dioptra of Philippos Monotropos. It focuses on the transmission of the Slavonic text. Furthermore, a critical edition of the prefaces and the first book of the poem, together with a Greek parallel text, is given.